The association between breast implants and anaplastic large cell lymphoma - a comprehensive review - Banach, Mariola; Miłek, Magdalena; Kwaśniak, Ksenia; Foryś, Angelika; Stawska, Weronika; Magierska, Agata; Ślusarczyk, Monika; Kotowicz, Zuzanna; Kmiotek, Weronika; Niemczyk, Anna (Quality in Sport, 2024)
Introduction and purpose: Recently, the topic of the incidence of breast implant-associated anaplastic large cell lymphoma has become very popular. The aetiology of the disease is not fully understood. Many women worldwide have undergone breast implant surgery, so raising awareness about the possibility of developing BIA-ALCL is crucial for early diagnosis. The aim of this article is to review and compile the currently available knowledge regarding the association of anaplastic large cell lymphoma with breast implants in patients who have undergone implant plastic surgery. Brief description of the state of knowledge: Literature data indicate a multifactorial aetiology of BIA-ALCL. Textured surface breast implants are suspected to be a significant risk factor, as they may lead to the development of chronic inflammation. The most common symptoms of BIA-ALCL include the accumulation of serous fluid around the breast implant, pain, swelling or breast asymmetry. A proper diagnostic and therapeutic process improves the prognosis. Material and methods: A comprehensive literature review was conducted using PubMed and Google Scholar databases. The search strategy was based on the following terms: BIA-ALCL; lymphoma; breast implants; textured implants. Conclusions: Although BIA-ALCL is a rare disease, it is important to know the risk factors and clinical signs that may suggest the disease. A proper diagnostic process allows the disease to be detected at an early stage and treated effectively. Knowledge of the occurrence of potential complications of implant surgery allows patients to take informed consent and increases vigilance on the part of clinicians.